Green Peafowl Sebagai Inspirasi Dalam Desain Busana Digital Evening Gown - Putri, Syilvi Karisa; Albahi, Haidarsyah Dwi; Budiono, Nadia Rachmaya Ningrum (Journal of Contemporary Indonesian Art, 2025)
This study describes the creative process of digital fashion design, focusing on how to transform the idea inspired by the Green Peafowl into an evening gown using digital design techniques. The motivation behind this creative work is the need for digital fashion designs that showcase contemporary fashion concepts as well as represent the beauty of the endemic Green Peafowl, a species currently threatened with extinction. The objective of this research is to create a digital fashion design inspired by the Green Peafowl, exploring its visual elements and aesthetics artistically in the form of an evening gown. Through the application of artistic theory and design principles, symbols representing the characteristics of the Green Peafowl—derived from visual elements such as shape, colour, and texture—are transformed into the design of the evening gown. The research method employed is Dharsono's artistic creation method, which consists of the following stages: 1) Observation, 2) Experimentation, 3) Reflection, and 4) Formation. The observation stage includes literature and pictorial studies related to the theme. The experimentation stage involves exploring the visual elements of the Green Peafowl in the design. The reflection stage involves analyzing and reflecting on the aesthetic aspects and meaning of the resulting design. The formation stage results in harmonious and innovative work in accordance with the concept and idea. The outcome of this research is a collection of digital evening gown designs. Penelitian ini mendeskripsikan proses kreatif pengkaryaan desain busana digital dengan fokus utama yakni; bagaimana mentranformasikan ide inspirasi Green Peafowl pada evening gown dengan teknik digitalisasi desain. Pengkaryaan ini didasari oleh kebutuhan akan desain busana digital untuk menampilkan konsep busana terkini, serta merepresentasikan keindahan fauna endemik Green Peafowl yang saat ini mulai terancam keberadaanya. Tujuan penelitian ini adalah menciptakan desain busana digital yang terinspirasi dari burung Green Peafowl, dengan mengeksplorasi elemen rupa dan estetika secara artistik ke dalam wujud evening gown. Melalui pendekatan teori artistik dan prinsip desain, simbol-simbol yang merepresentasikan karakteristik Green Peafowl, bersumber dari elemen rupa seperti bentuk, warna, dan tekstur, ditransformasikan kedalam wujud evening gown. Metode penelitian yang digunakan adalah kreasi artistik Dharsono, dengan tahapan proses yakni; 1) Observasi, 2) eksperimen, 3) perenungan, dan 4) pembentukan. Tahap Observasi meliputi studi pustaka dan piktorial terkait tema yang diusung. Tahap eksperimen dilakukan dengan mengeksplorasi elemen rupa Green Peafowl ke dalam desain. Tahap perenungan melibatkan analisis dan refleksi terhadap aspek estetika dan makna dari desain yang dihasilkan. Tahap pembentukan menghasilkan karya yang harmonis dan inovatif sesuai konsep dan gagasan ide. Hasil penelitian ini berupa koleksi desain busana digital evening gown.